Floods in a changing climate : inundation modelling - Di Baldassarre, Giuliano, 1978- (Cambridge, UK. : Cambridge University Press, 2012)
'Flood inundation models enable us to make hazard predictions for floodplains, mitigating increasing flood fatalities and losses. This book provides an understanding of hydraulic modelling and floodplain dynamics, with a key focus on state-of-the-art remote sensing data, and methods to estimate and communicate uncertainty. Academic researchers in the fields of hydrology, climate change, environmental science and natural hazards, and professionals and policy-makers working in flood risk mitigation, hydraulic engineering and remote sensing will find this an invaluable resource. This volume is the third in a collection of four books on flood disaster management theory and practice within the context of anthropogenic climate change. The others are: Floods in a Changing Climate: Extreme Precipitation by Ramesh Teegavarapu, Floods in a Changing Climate: Hydrological Modeling by P.P. Mujumdar and D. Nagesh Kumar and Floods in a Changing Climate: Risk Management by Slodoban Simonovi{u28E2}--
'Floodplains are among the most valuable ecosystems for supporting biodiversity and providing environmental services, and are also home to approximately one-sixth of the world population. As a result, flood disasters currently affect more than 100 million people a year. Flood inundation models are a valuable tool in mitigating increasing flood fatalities and losses. This book demonstrates how these models enable us to make hazard predictions for floodplains, support appropriate land-use and urban planning, and help discourage new human settlements in flood prone areas. It provides an understanding of hydraulic modelling and floodplain dynamics, with a key focus on state-of-the-art remote sensing data, and methods to estimate and communicate uncertainty. Additional software and data tools to support the book are accessible online at www.cambridge.org/dibaldassarre'--
Includes bibliographical references (pages 97-102) and index.
Keywords: Flood damage prevention; Floodplain management; Floodplains; Hydrogeological modeling; Climatic changes -- Environmental aspects